Pengaruh Tangibility Asset, Size, dan Volatilitas Terhadap Financial Distress Pada Bumn di Bursa Efek Indonesia - Alvita, Devi; Kusumawardhani, Ratih; Sari, Pristin Prima (Universitas Nahdlatul Ulama Blitar, 2024)
This research aims to determine the effect of asset tangibility, size and volatility on financial distress. In estimating financial distress in this research, the Altman Z-score model was used. With a sample size of 27 state-owned companies for 4 years or during COVID-19. The results of the analysis obtained are that the asset tangibility variable states that it has no effect on financial distress. Because, a high asset tangibility value will not necessarily prevent the company from financial distress. The size variable shows that it has no effect on financial distress. Companies that have a large number of assets will not necessarily avoid financial distress or financial difficulties. The volatility variable shows an influence on financial distress. Companies that have low volatility values ​​do not necessarily always experience financial distress or financial difficulties, and vice versa. This is because the volatility value will affect investors who will invest. This research concludes that state-owned companies listed on the Indonesia Stock Exchange for the 2019-2022 period or during the COVID-19 pandemic did not have a significant influence on financial distress. However, during COVID-19, banking and health companies made very rapid profits.